Interpersonal communication and psychological well-being among couples coping with sensory loss: The mediating role of perceived spouse support. (August 2019) - Hofsöe, Sofia Maria; Lehane, Christine M.; Wittich, Walter; Hilpert, Peter; Dammeyer, Jesper
Couples who are willing to discuss sensory loss-related issues typically report better well-being, while couples who avoid such discussions tend to report poorer well-being. Inspired by the relationship intimacy model, the present study examined whether the link between couples' sensory loss-related communication and well-being can be explained by perceived spouse support and whether this mediation mechanism is stable over time. Adults with sensory loss (AWSLs) and their spouses ( N = 206 individuals) completed an online survey and were followed up 6 months later. A multi-group actor–partner interdependence mediation model was used to test the mediation mechanism as well as its stability over time. Results showed that the association between couples' willingness to communicate about the sensory loss and psychological well-being was mediated by perceived spouse support for AWSLs only. Furthermore, this mediation effect remained stable over the 6-month period. These results support prior research that the manner in which couples communicate about the sensory loss is important for their well-being. However, because perceived spouse support was not found to mediate the association for spouses, future studies should investigate other factors as potential mediating mechanisms among spouses of adults with sensory loss.